DEPRECIATION: THE OFFSETTING-INTEREST METHOD. - Sosnick, Stephen H. (The Accounting Review, 1962)
Abstract This paper makes four points: (1) The justification of interest methods of depreciation is not attainment of a constant operating rate of return; rather, they are the only time-based methods of depreciation that (a) can avoid showing changes in reported net earnings over the life of the asset simply because recovered "depreciation funds" can interest, (b) can disclose the amount that can legitimately be paid out in dividends, and (c) can maintain parity between renting and buying fixed assets. (2) For these purposes the formula usually given for "the interest method" applies only to a special case. (3) It is easy to avoid the principal disadvantage of the interest method-neglect of increasing maintenance costs-by creating a surplus reserve according to certain formulas. (4) Price-level adjustments can be incorporated easily if desired, but the procedure usually used is valid only for a special case. It is often said that the principal reason for charging depreciation as a current expense is to allocate the cost of long-lived assets to individual accounting periods. But this is depreciation. The question remains:Why is it reasonable?